Tinjauan Yuridis Jual Beli Sawit Antara Pemasok Sawit Dengan Masyarakat Aek Torop Desa Asam Jawa - Nadya Francela Hasibuan; Zaini Munawir; Windy Sri Wahyuni (Universitas Medan Area, 2021)
The purpose of this research is: to find out how the form of sale and purchase agreement between toke oil palm and the people of Aek Torop, Asamjawa Village, Torgamba Labuhanbatu Selatan District in accordance with Article 1320 of the Civil Code and to find out what the forms of rights and obligations and the termination of the sale and purchase agreement between toke oil palm and the Aek community Torop Asamjawa Village, Torgamba South Labuhanbatu District. The type of research the writer uses is normative legal research. The results showed that the form of agreement made by the supplier (toke) with the Aek Torop Community, Asamjawa Village, Torgamba South Labuhanbatu District is a direct agreement system, where the agreement is made through a face-to-face process, and the validity of the agreement is made by shaking hands. The contents of the agreement are the terms of price and payment system that will be carried out by both parties. The form of rights and obligations that must be carried out by both parties is to give the harvest (palm oil) to the toke and pay the harvest (palm) which has been weighed according to the agreed price. The agreement ends when the farmers give their crops and the supplier pays the scales according to the set price.